Development and Classroom Evaluation of an Interactive E-Module for Islamic Religious Education in an Indonesian Junior Secondary School - Fauzan, M.; Supratman, Supratman; Rahmadhani, Riri (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2026)
This study developed an interactive e-module for Grade VIII Islamic Religious Education (IRE) at SMP Negeri 2 Padang Panjang and examined its validity, practicality, and learning-outcome evidence during classroom implementation. The study used a research and development design based on the ADDIE model: analysis, design, development, implementation, and evaluation. The e-module addressed the Abbasid period and integrated structured content, images, audio, videos, navigation features, exercises, and a final evaluation. It was reviewed by two subject-matter experts, two language experts, and two media experts. Classroom implementation involved 52 students in two intact Grade VIII classes: an experimental group (n = 26) and a control group (n = 26). The average Aiken’s V value was .90, indicating high expert agreement regarding the content, language, and media design. Teacher and student questionnaire responses produced a Fleiss’ Kappa value of 1.00, indicating complete consistency in the reported response categories. The experimental group’s mean score increased from 72.88 on the pretest to 92.31 on the posttest, whereas the control group increased from 60.77 to 76.35. The experimental group also obtained a higher N-gain (.73) than the control group (.38). However, the groups differed significantly at pretest and were not randomly assigned. Therefore, the findings indicate that the e-module was feasible for the participating classroom setting and was associated with higher observed learning outcomes, rather than establishing a conclusive causal effect.